2022
DOI: 10.3390/molecules27165184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Silver and Graphene Nanocomposites and Their Antimicrobial and Photocatalytic Potentials

Abstract: Microbial pathogens and bulk amounts of industrial toxic wastes in water are an alarming situation to humans and a continuous threat to aquatic life. In this study, multifunctional silver and graphene nanocomposites (Ag)1−x(GNPs)x [25% (x = 0.25), 50% (x = 0.50) and 75% (x = 0.75) of GNPs] were synthesized via ex situ approach. Further, the synthesized nanocomposites were explored for their physicochemical characteristics, such as vibrational modes (Raman spectroscopic analysis), optical properties (UV visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…As schematically illustrated in Figure 1 and Supplementary Materials Figure S2 , a 3D reduced graphene oxide (3D rGO) scaffold was synthesized through a modified hydrothermal process followed by a freeze-drying process [ 29 ]. To obtain 3D reduced graphene oxide (rGOA), the first step was to use a modified Hummer’s process to synthesize graphene oxide (GO) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As schematically illustrated in Figure 1 and Supplementary Materials Figure S2 , a 3D reduced graphene oxide (3D rGO) scaffold was synthesized through a modified hydrothermal process followed by a freeze-drying process [ 29 ]. To obtain 3D reduced graphene oxide (rGOA), the first step was to use a modified Hummer’s process to synthesize graphene oxide (GO) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, previous research showed AgNPs alone showed less inhibition in all three bacterial strains as compared to Ag-GNPs nanocomposites. Among all Ag-GNPs nanocomposites, 50% GNPs-Ag are more towards inhibiting pathogens, i.e., 28.78% ( E. coli ), 31.34% ( S. aureus ) and 30.31% ( P. aeruginosa ) as compared to AgNPs, i.e., 19.78% ( E. coli ), 17.91% ( S. aureus ) and 20.97% ( P. aeruginosa ), respectively [ 29 ]. Additionally, these scattered nanocomposites did not exist as three-dimensional entities, so it was difficult to collect the Ag–GO nanocomposite from water after antibacterial processes, which was not conducive to the reuse of antibacterial agent as well as the environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Section 3 , the shortcomings of metal nanoparticles limit their potential for medical applications. To overcome these issues, many nanocomposites composed of metal nanoparticles and graphene have been prepared experimentally and studied against various bacterial strains [ 287 , 288 , 289 , 290 , 291 , 292 ]. Some of the available literature reviewed the development of graphene–metal matrix nanocomposites which will not be repeated here [ 293 , 294 , 295 , 296 ].…”
Section: Nanocomposite/nanohybrid Antibacterial Materialsmentioning
confidence: 99%
“…The enhanced antibacterial activity of GO–Ag nanocomposites is often ascribed to the synergistic activity of GO and Ag; however, the full antibacterial mechanism remains to be elucidated [ 299 ]. Malik et al have also demonstrated that GO–Ag nanocomposites exhibit significantly enhanced growth inhibition of E. coli , S. aureus , and P. aeruginosa relative to silver nanoparticles alone [ 291 ]. Recent studies have accomplished the surface functionalization of GO and Ag nanoparticles by using lantana plant extract, and the results also affirmed the potential of GO–Ag nanocomposites as antibacterial agents against biological pollutants [ 290 ].…”
Section: Nanocomposite/nanohybrid Antibacterial Materialsmentioning
confidence: 99%
See 1 more Smart Citation